Spider species richness is driven by insect diversity rather than habitat complexity in the understory of the Brazilian Cerrado - Reis, Jéssica Silva dos; Tizo, Alinne Ferreira Silva; Barroso, Renata de Freitas; Pereira, Vitória Luiza Cardoso; de Deus, Marcos Henrique André; Pedroso, Everton Tizo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
Habitat complexity is determined by the variation of physical and biological components within an environment. More complex habitats generally provide a greater diversity of shelters, food, and reproduction sites, contributing to richer biodiversity. In this study, we investigated how habitat complexity, provided by understory plants in natural areas of the Brazilian Cerrado, influences spider species richness. We assessed structural variables such as leaf number, plant size, and herbivory incidence, as well as prey availability measured by insect richness. Our results revealed that spider richness was positively correlated with insect richness, highlighting the role of prey diversity in supporting predator communities. However, an inverse relationship between spider richness and leaf number suggests that denser foliage may limit accessibility for some spider species or favor dominance by specialists. These findings emphasize the importance of conservation strategies focused on preserving plant diversity and structural heterogeneity to maintain ecological balance and biodiversity in the Cerrado.
Keywords: Arachnida; Tropical savanna; Habitat structure; Cerrado conservation; Spider richness